Cortically based cystic supratentorial RELA fusion-positive ependymoma: a case report with unusual presentation and appearance and review of literature - Yasmine T. Sallam, MD; Qi Zhang, MBBS, PHD, FRCPC; Sachin K. Pandey, MD, FRCPC (Radiology Case Reports, 2020)
Ependymomas are rare central nervous system tumors that can arise anywhere in the neuroaxis. Supratentorial and posterior fossa ependymomas were identified as distinct diseases after extensive molecular analysis. The 2016 World Health Organization update further introduced RELA fusion-positive ependymoma as a novel entity as a subset of supratentorial ependymomas indicating the presence of C11orf95-RELA fusion genes. RELA fusion-positive ependymomas are commonly intraventricular, though they may rarely manifest as extraventricular, cortically-based tumors. They are commonly large solid, mixed solid/cystic tumors or rarely cystic. In this paper, we report a case of RELA fusion positive cortically based-cystic ependymoma and review the existing literature. Our patient is a 9-year-old boy who presented with an unusual presentation of right facial droop. He underwent gross total resection of the ependymoma, following resection, his facial droop resolved and there was no neurologic deficit.